The Role of Librarians in Empowering Diponegoro University's Digital Library as an Online Learning Resource - Safina Candra Kirana Wardani; Ika Krismayani (Prodi S1 Ilmu Perpustakaan dan Informasi, Fakultas Ilmu Budaya, Universitas Diponegoro, 2025)
This study aims to determine the role of librarians in empowering Diponegoro University's digital library as a learning resource for online lectures. In this study the writer used case method with a descriptive approach. The informant selection technique used was purposive sampling. Data collection methods were carried out through observation, interviews and documentation. Data analysis method was done through data reduction, data presentation and conclusion drawing or verification. The results of this study show that the three main roles of the Diponegoro University's Library librarians during online lectures, namely as administrators and managers, information and reference providers and assistants and facilitators. They are responsible as administrators, information providers and student companions by ensuring the best service, providing references, assisting users in utilizing digital libraries. Thus, Diponegoro University's Library librarians have contributed to the success of online lectures and effective users of learning resources.